2007
DOI: 10.1111/j.1744-7429.2006.00257.x
|View full text |Cite
|
Sign up to set email alerts
|

Upland Soil Charcoal in the Wet Tropical Forests of Central Guyana

Abstract: A soil charcoal survey was undertaken across 60,000 ha of closed-canopy tropical forest in central Guyana to determine the occurrence, ubiquity, and age of past forest fires across a range of terra firme soil types. Samples were clustered around six centers consisting of spatially nested sample stations. Most charcoal was found between 40 and 60 cm depth with fewest samples yielding material at 0-20 cm depth. The first core yielded charcoal at most stations. Charcoal ages of a random subsample ranged from less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
2
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 39 publications
6
29
2
3
Order By: Relevance
“…Our findings are at odds with neotropical fire-history reconstructions from lowland forests and from Central American savanna environments that show maximum fire activity during this period (18,19,21,22,24,25). For example, documented high pre-Columbian fire activity in rainforest of neighboring central Guyana (29) is not reflected in the K-VIII core. The low charcoal abundance in zone K-VIII-2 is most parsimoniously explained by the implementation of fire limitation practices by pre-Columbian raised-field farmers, especially because our study area is characterized by a long dry season and commensurate high fire probability (30).…”
Section: Resultscontrasting
confidence: 55%
“…Our findings are at odds with neotropical fire-history reconstructions from lowland forests and from Central American savanna environments that show maximum fire activity during this period (18,19,21,22,24,25). For example, documented high pre-Columbian fire activity in rainforest of neighboring central Guyana (29) is not reflected in the K-VIII core. The low charcoal abundance in zone K-VIII-2 is most parsimoniously explained by the implementation of fire limitation practices by pre-Columbian raised-field farmers, especially because our study area is characterized by a long dry season and commensurate high fire probability (30).…”
Section: Resultscontrasting
confidence: 55%
“…the CO 2 increase after 8000 cal years BP recorded in Taylor Dome, Antarctica, IndermĂŒhle et al, 1999). The presence of charcoal as an indicator of vegetation burning has been found in soils (Soubies, 1980;Sanford et al, 1985;Saldarriaga and West, 1986;Bassini and Becker, 1990;Piperno and Becker, 1996;Pessenda et al, 1998a;Santos et al, 2001;Hammond et al, 2006) and lake sediments (Sifeddine et al, 1994;Cordeiro, 1995;Cordeiro et al, 1997;Irion et al, 2006;Cordeiro et al, 2008) at various Amazonian sites and has been interpreted classically as a consequence of dry climates associated with increasing human presence.…”
Section: Introductionmentioning
confidence: 95%
“…Although, globally, fire has been mostly driven by climate until recent times , the situation in the Neotropics differs substantially due to the anthropogenic nature of most fire events (Shlisky et al, 2009). Some paleoecological studies have shown evidence of fires related to human populations in NE Amazonia since at least 8000 cal yr BP (Hammond et al, 2006;Bush et al, 2007). Moreover, although there is a general lack of paleo-fire records in the Neotropics, several studies have revealed the presence of paleo-fires in northern South America during the Holocene, probably related to a climate (mainly El Niño Southern Oscillation intensification and solar insolation) and human impact synergism (Sanford et al,1985;Hammond et al, 2006;Bush et al, 2008).…”
Section: Introductionmentioning
confidence: 99%